Historical overview of quinine isolation and its importance - Jovanović, Aleksandar; Krajnović, Dušanka (Archives of Pharmacy, 2022)
The use of quinine bark was first documented in 1630 by Jesuit missionaries, after which it occupied the great attention of scientists. In 1746 Count Claude Toussaint Marot de la Garaye was the first to crystallize a substance from quinine bark and called it "sel essentiel de quinquina", which was later found to have no clinical effects. With the development of acid-base extraction procedures, in 1820, two French scientists, pharmacists Pierre Pelletier and Joseph Caventou, isolated the active substance and called it quinine. They used the "yellow" bark of quinine, which was known to be more effective against malaria than the "gray" bark used by scientists in previous attempts at isolation. Having received numerous awards and honors, these two scientists established a factory in Paris for the extraction of quinine, an activity that is often mentioned as the beginning of the modern pharmaceutical industry. After isolation, doctors confirmed its efficacy and specificity in the treatment of malarial fever, making quinine preparations become part of the official Materia medica. Isolation enabled quantitative assessment of bark quality, more precise dosing and higher efficiency. Quinidine, cinchonine and cinchonidine are isolated after quinine, and the effectiveness of these four alkaloids was evaluated in one of the earliest clinical trials, conducted from 1866 to 1868 on 3,600 subjects. Quinine is included in a number of pharmacopoeias, and the Pharmacopée universelle describes more than 100 official quinine-based preparations for the treatment of a large number of diseases.